Gem-TIP as a salvage therapy for pediatric extracranial malignant rhabdoid tumors: insights from a retrospective case series - Jian Li; Lulu He; Tianjiao Hu; Xinrong Lin; Qian Zhao; Qiyang Shen; Jianfeng Zhou; Tao Li; Li Zhou (BMC Cancer)
Abstract Objective This retrospective case series aimed to provide initial insights into the potential effectsof Gemcitabine (Gem), Nab-paclitaxel, Ifosfamide, and Cisplatin (Gem-TIP) combination therapy in children with relapsed/progressive extracranial malignant rhabdoid tumors (eMRTs). Methods A retrospective review of patients treated with Gem-TIP following relapse/progression was conducted. Radiologic responses were assessed using RECIST 1.1 criteria, with supplemental imaging data provided for detailed evaluation. Details of concurrent therapies, including radiotherapy, were documented to better delineate their influence on treatment outcomes. Results Ten patients were included, with a median age of 29.5 months at diagnosis. Tumor origins were predominantly renal (8 cases). Patients received a median of 3.1 cycles of Gem-TIP. The overall response rate (ORR) was 40% (1 CR, 3 PR), and the disease control rate (DCR) was 70%. Median event-free survival (EFS) and overall survival (OS) were 4 and 7.5 months, respectively. Radiotherapy and secondary surgery administered to 3 patients after Gem-TIP chemotherapy, likely contributed to improved local control. Toxicities included grade 4 neutropenia (50%) and thrombocytopenia (70%). However, limited data on hearing evaluation due to the retrospective design was noted. Conclusions Gem-TIP chemotherapy demonstrated preliminary evidence of therapeutic activity in relapsed/progressive eMRTs, but its role requires to be verified by large, prospective multi-center studies of rigorous design.